Oxidative stress mediates the pathogenic effect of different Alzheimer's disease risk factors - Guglielmotto, Michela; Giliberto, Luca; Tamagno, Elena; Tabaton, Massimo (Frontiers in Aging Neuroscience, 2010)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder affecting the elderly population. Mechanistically, the major cause of the disease bases on the altered processing of the amyloid-β (Aβ) precursor protein (APP), resulting in the accumulation and aggregation of neurotoxic forms of Aβ. Aβ derives from the sequential proteolytic cleavage of the β- and γ-secretases on APP. The causes of Aβ accumulation in the common sporadic form of Alzheimer’s disease are not completely known, but they are likely to include oxidative stress (OS). OS and Aβ are linked to each other since Aβ aggregation induces OS in vivo and in vitro, and oxidant agents increase the production of Aβ. Moreover, OS produces several effects that may contribute to synaptic function and cell death in AD. We and others have shown that the expression and activity of β-secretase (named BACE1; β-site APP cleaving enzyme) is increased by oxidant agents and by lipid peroxidation product 4-hydroxynonenal and that there is a significant correlation between BACE1 activity and oxidative markers in sporadic AD. OS results from several cellular insults such as aging, hyperglycaemia, hypoxic insults that are all well known risk factors for AD development. Thus, our data strengthen the hypothesis that OS is a basic common pathway of Aβ accumulation, common to different AD risk factors.